64.2k views
0 votes
How do I solve this?​

How do I solve this?​-example-1
User Elior
by
5.0k points

1 Answer

1 vote

Answer:


x = (6 - a)/(a + 3)

Explanation:


(3x - 2)/(a^2 - 2a) + (x - 1)/(a - 2) + (2)/(a) = 0

Factor all denominators.


(3x - 2)/(a(a - 2)) + (x - 1)/(a - 2) + (2)/(a) = 0

There are 3 denominators: a(a - 2), a - 2, and a.

The LCD is a(a - 2).

Multiply both sides of the equation by the LCD.


a(a - 2)[(3x - 2)/(a(a - 2)) + (x - 1)/(a - 2) + (2)/(a)] = 0 * a(a - 2)


a(a - 2) * (3x - 2)/(a(a - 2)) + a(a - 2) * (x - 1)/(a - 2) + a(a - 2) * (2)/(a)] = 0


3x - 2 + a(x - 1) + 2(a - 2) = 0


3x - 2 + ax - a + 2a - 4 = 0


3x + ax + a - 6 = 0


x(a + 3) = 6 - a


x = (6 - a)/(a + 3)

User CTMacUser
by
4.7k points